Outcome prediction models in AQP4-IgG positive neuromyelitis optica spectrum disorders - Palace, Jacqueline (Brain, 2019)
Pathogenic antibodies targeting the aquaporin-4 water channel on astrocytes are associated with relapsing inflammatory neuromyelitis optica spectrum disorders. The clinical phenotype is characterized by recurrent episodes of optic neuritis, longitudinally extensive transverse myelitis, area postrema attacks and less common brainstem and cerebral events. Patients often develop major residual disability from these attacks, so early diagnosis and initiation of attackpreventing medications is important. Accurate prediction of relapse would assist physicians in counselling patients, planning treatment and designing clinical trials. We used a large multicentre dataset of 441 patients from the UK, USA, Japan and Martinique who collectively experienced 1976 attacks, and applied sophisticated mathematical modelling to predict likelihood of relapse and disability at different time points. We found that Japanese patients had a lower risk of subsequent attacks except for brainstem and cerebral events, with an overall relative relapse risk of 0.681 (P = 0.001) compared to Caucasians and African patients, who had a higher likelihood of cerebral attacks, with a relative relapse risk of 3.309 (P = 0.009) compared to Caucasians. Female patients had a higher chance of relapse than male patients (P = 0.009), and patients with younger age of onset were more likely to have optic neuritis relapses (P < 0.001). Immunosuppressant drugs reduced and multiple sclerosis disease-modifying agents increased the likelihood of relapse (P < 0.001). Patients with optic neuritis at onset were more likely to develop blindness (P < 0.001), and those with older age of onset were more likely to develop ambulatory disability. Only 25% of long-term disability was related to initial onset attack, indicating the importance of early attack prevention. With respect to selection of patients for clinical trial design, there would be no gain in power by selecting recent onset patients and only a small gain by selecting patients with recent high disease activity. We provide risk estimates of relapse and disability for patients diagnosed and treated with immunosuppressive treatments over the subsequent 2, 3, 5 and 10 years according to type of attack at onset or the first 2-year course, ethnicity, sex and onset age. This study supports significant effects of onset age, onset phenotype and ethnicity on neuromyelitis optica spectrum disorders outcomes. Our results suggest that powering clinical treatment trials based upon relapse activity in the preceding 2 years may offer little benefit in the way of attack risk yet severely hamper clinical trial success.